Penggunaan Akronim dan Singkatan di Media Sosial Twitter/X pada Akun @Tubirfess - Rofiq, Muhammad Anis; Amri, Muhammad Daffa; Neina, Qurrota Ayu (Institut Nalanda, 2026)
This study investigates the linguistic construction, pragmatic functions, and sociocultural implications of acronyms and abbreviations used by Indonesian youth in the comment section of the Twitter/X account @Tubirfess. The research aims to classify the structural patterns of these abbreviated forms and to analyze how they operate within the dynamics of digital communication. Employing a qualitative descriptive design, the data were compiled through purposive sampling from one hundred user comments collected between September and November 2025. The data analysis consisted of reduction, classification, presentation, and interpretative stages aligned with qualitative analytical procedures. The findings reveal that highly frequent forms such as OTW, BTW, GWS, and VIP demonstrate a dual function, linguistic and sociolinguistic identity marking. These forms not only illustrate users’ tendency to maximize communicative efficiency but also function as symbolic resources that articulate emotional positioning, interpersonal intimacy, and group affiliation in virtual communities. The dominance of hybrid forms combining Indonesian and English indicates an ongoing linguistic adaptation shaped by technological, cultural, and generational demands. This study concludes that acronyms and abbreviations have become integral elements of digital discourse, influencing the evolution of written Indonesian while simultaneously reflecting the expressive and interactional practices of contemporary digital youth culture.